Tools for Effective Regulation: Is "More" Always "Better"?. (25th May 2018) - BLANC, Florentin
Abstract: Regulatory inspections and enforcement are seen by many as a key instrument to ensure the effectiveness of regulations – it is broadly assumed to be essential to have supervision and "deterrence" to promote compliance with rules, and thus achievement of regulatory outcomes. However, this presupposes that rules are indeed adequate for reaching outcomes, and that control is what drives compliance with rules. A different approach suggests that compliance is more complex and driven by a combination of factors (ethics, social conformity, procedural justice and legitimacy etc), that rules are imperfect, and that risk-focused, risk-proportionate "regulatory delivery" will achieve better results, more "effectiveness". Considering a case study of occupational safety inspections and outcomes in Britain, France and Germany, we observe that higher numbers of inspections are not correlated with less fatal incidents, and that, on the contrary, the best outcomes are achieved in the country having the least inspection visits, the most risk-focused system, and the broadest approach to "regulatory delivery", combining engagement with regulated industries, guidance, responsive and risk-proportionate enforcement, and risk-based, targeted inspections.